1996
DOI: 10.1038/ki.1996.296
|View full text |Cite
|
Sign up to set email alerts
|

High resolution localization of endothelin receptors in rat renal medulla

Abstract: The cellular localization of endothelin receptors in the inner medulla of the rat kidney was investigated by using high resolution light and electron microscopic autoradiography, with the microwave irradiation fixation methods. Kidney slices were incubated with 125I-endothelin-1 alone or with selective ligands for the endothelin ETB and/or ETA receptors for light microscopic autoradiography. At the microscopic level, 125I-endothelin-1 was found to bind specifically to the glomeruli, arterioles and peritubular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…These membranes are known to contain Na + , K + -ATPase. In agreement with our data, ET binding sites have also been demonstrated on basal infoldings of these cells by a radiobinding study (Yukimura et al, 1996). Thus, the ETA receptor may be involved in the ET-mediating reduction of Na + , K + -ATPase activity.…”
Section: Discussionsupporting
confidence: 79%
“…These membranes are known to contain Na + , K + -ATPase. In agreement with our data, ET binding sites have also been demonstrated on basal infoldings of these cells by a radiobinding study (Yukimura et al, 1996). Thus, the ETA receptor may be involved in the ET-mediating reduction of Na + , K + -ATPase activity.…”
Section: Discussionsupporting
confidence: 79%
“…Numerous studies involving multiple species and techniques consistently demonstrate that the CD is the major renal site of ET receptor expression (16,101,103,113). As for ET-1 production, the highest binding of ET-1 is in IMCD, followed by OMCD and CCD (88).…”
Section: Expression and Regulation Of Collecting Duct Et Receptorsmentioning
confidence: 94%
“…Concurringly, these studies identified the glomeruli, longitudinal I-ET-1 binding, Interglomerular regions showed only sparse labeling, and the outer stripe of the outer medulla was completely negative (Davenport et al 1989;Kohzuki et al 1989). However, data are inconsistent concerning the determination of cellular binding sites by high-resolution light and electron microscopy (Furuya et al 1992;Dean et al 1994Dean et al ,1996Yukimura et al 1996). Furthermore, the design of these autoradiographic studies did not allow discrimination between receptor subtypes.…”
mentioning
confidence: 99%
“…Few autoradiographic studies have addressed this issue by use of unlabeled ET-receptor-subtype-specific ligands. Using 125 I-ET-1 binding in the presence of excess of unlabeled ET A or ET B receptor ligands, Yukimura et al (1996), as well as Dean et al (1996), reported that the ET B receptor agonist sarafotoxin S6c abolishes 125 I-ET-1 binding almost completely with exception of binding to the inner medulla, which also could not be abolished by a combination of ET A and ET B receptor antagonists.…”
mentioning
confidence: 99%